TAYANGAN MUKBANG DAN PERILAKU KESEHATAN DEWASA MUDA: TINJAUAN LITERATUR - Dwi Meitasari; Dien Anshari (Poltekkes Kemenkes Bandung, 2023)
Mukbang is a trend that originates from Korea where someone shows eating (usually in large quantities) broadcast live (live streamed) or pre-recorded and watched by an audience. Watching mukbang is often associated with nutritional problems which have an impact on obesity rates. Where obesity rates have increased significantly from year to year. This study aimed to determine the relationship between watching mukbang and nutritional status, especially in adults. The method used in this research is a literature review by analyzing 7 selected articles based on inclusion and exclusion criteria obtained from several e-databases, namely Proquest, Sage, Scopus, Google Scholar and Garuda. The results of the study showed that there was no statistically significant relationship between watching mukbang and nutritional status. However, there are several other variables that are directly related to nutritional status, namely appetite, body image, eating patterns and nutritional knowledge. The conclusion obtained is that although mukbang is not significantly related to nutritional status, there are other variables that are related to mukbang, namely desire to eat, eating preferences, eating disorders, internet addiction, health habits, eating behavior, perceived value and increasing impulsive buying and consumption, as well as excessive consumption.